Environmentally Friendly Human Resource Management in Organizational Transformation: The Role of Gender and Culture in Sustainability and Inclusive Performance - Ahmad Karim; Prayoga, Boby Indra; Paroli (Universitas Brawijaya, Indonesia, 2025)
Issues of sustainability and inclusivity in public organizations are increasingly driving innovation in human resource management. This study aims to analyze the influence of Green Human Resource Management (GHRM) on inclusive performance and organizational sustainability, considering the mediating role of environmental commitment and the moderating roles of gender and organizational culture. This study uses an explanatory quantitative approach with a population of civil servants (ASN) in the Medan City Government. The sampling technique employed was purposive sampling, involving 222 respondents, and data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) in SmartPLS. The results show that GHRM has a positive effect on inclusive performance and environmental commitment, but does not directly affect organizational sustainability. Ecological responsibility plays a significant mediating role in strengthening the influence of GHRM on both outcomes. In addition, gender moderates the relationship between GHRM and organizational sustainability, while organizational culture moderates the relationship between GHRM and inclusive performance. Theoretically, this study extends the application of the Ability-Motivation-Opportunity (AMO) Theory and Social Exchange Theory to the context of the Indonesian public bureaucracy. These findings indicate that the success of GHRM is highly dependent on social dimensions, such as ecological commitment, gender inclusiveness, and a collaborative organizational culture. These findings confirm that integrating green values into public HR policies can improve inclusive performance and organizational sustainability, mainly when supported by green leadership, participatory reward systems, and an adaptive and gender-equitable work culture.